2007
DOI: 10.1002/chem.200601244
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Relativistic DFT and Ab Initio Study on the Structure and Thermodynamics of the Oxofluorides of Uranium(IV), (V) and (VI)

Abstract: All the possible uranium(VI, V, IV) oxides, fluorides and oxofluorides were studied theoretically by using density functional theory (DFT) in the generalised gradient approximation (GGA), and three different relativistic methods (all-electron scalar four component Dyall RESC method (AE), relativistic small-core ECPs, and zeroth order regular approximation ZORA). In order to test different correlation methods, for the two former relativistic methods hybrid DFT, and, for the AE method, MP2 molecular orbital calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
223
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(244 citation statements)
references
References 72 publications
(121 reference statements)
20
223
0
Order By: Relevance
“…[65,[69][70][71][72][73][74] Careful comparison with other relativistic methods as implemented in codes such as Gaussian 03 and ADF confirmed that Priroda is entirely reliable for actinide complexes. [65,[69][70][71] Very recently, investigations of binuclear UO 2 2 + ···M 2 + (An = U, Np and Pu; M = Mn, Fe, Co and Zn) complexes have given reasonable agreement with experimental results. [74] Scheme 1.…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…[65,[69][70][71][72][73][74] Careful comparison with other relativistic methods as implemented in codes such as Gaussian 03 and ADF confirmed that Priroda is entirely reliable for actinide complexes. [65,[69][70][71] Very recently, investigations of binuclear UO 2 2 + ···M 2 + (An = U, Np and Pu; M = Mn, Fe, Co and Zn) complexes have given reasonable agreement with experimental results. [74] Scheme 1.…”
Section: Methodsmentioning
confidence: 55%
“…here to slightly underestimate bond strengths and corresponding stretching frequencies [69][70][71]86] ) and similar to those at 895-907 cm À1 for [{(thf)UO 2 ···MA C H T U N G T R E N N U N G (thf)}(L)] (M = Mn, Fe and Co), [25] 830 and 933 cm À1 for [UO 2 …”
Section: ···Ma C H T U N G T R E N N U N G (Thf)}(l)] (M = Mn and Co)mentioning
confidence: 51%
“…12 As for issues (i) and (ii), hybrid DFT and small-core relativistic effective core potentials (ECPs) or all-electron relativistic treatments such as the zeroth-order regular approximation (ZORA) have proven fairly robust in describing the thermochemistry of actinides. 13 Because 1 is a closed-shell f 0 system, spin-orbit coupling can safely be neglected. Based on these considerations, there is little reason to doubt the accuracy, at least in a qualitative sense, of Shamov and Schreckenbach's results for 1.…”
Section: Methodsmentioning
confidence: 99%
“…For the thermochemistry of reactions involving the uranyl unit, hybrid functionals such as B3LYP tend to perform better than pure GGAs (such as BLYP). 13 Unfortunately, CPMD is impracticable with hybrids. Since our CPMD/BLYP-derived overall barrier is related to the relative stability of cis-and trans-uranyl hydroxide, however, to a first approximation we can use the static energetic data from Table 1 as incremental corrections to the barrier.…”
Section: -17mentioning
confidence: 99%
“…pure, gradient corrected functionals, which are sometimes outperformed by hybrid variants when it comes to reaction energies involving actinides. 26 As mentioned above, in the CPMD/PTI studies of aqueous uranyl complexes BLYP has performed quite well so far, but if it turns out to fail for the aquo tetrafluoro complex, the predictive power of this approach may be at stake. An utter failure would for instance be the incorrect prediction that 1a should also be unstable in the environment of a known, stable crystal.…”
Section: Introductionmentioning
confidence: 99%